A PHOTOBIOREACTOR FOR MICROALGAE-BASED WASTEWATER TREATMENT - Pavliukh, Lesia; Shamanskyi , Sergii (Proceedings of National Aviation University (archive), 2021)
Purpose and Objectives of the Work. This scientific article is devoted to creation of an advanced photobioreactor design for wastewater treatment from biogenic compounds. Research Methods are based on a systematic analysis of theoretical research, synthesis, anology and comparison. Research Results. As a result, the improved photobioreactor design was proposed, in which the application of new elements and connections reduces the required area for its placement, immobilization of microalgae in the working area and, as a result, reducing the working area, the ability to quickly replace the sleeves of the working area, covered with sediment inside, and, as a result, reduce labor costs and downtime of the photobioreactor. Discussion. The problem is solved by the fact that the photobioreactor is made in the form of a transparent flowing rectangular open-topped tank, inside of which are vertically attached to the bottom of the tank by quick-release fasteners transparent flowing flexible hoses, to which at the bottom by means of non-return valves are connected pipelines for wastewater and microalgae supply and tubes for carbon dioxide supply and are connected by means of shut-off valves pipelines for drainage of a mixture of microalgae with residual wastewater, and in the upper hermetic part, where there are valves for drainage of accumulated gases , while the pipeline for the purified wastewater discharge is connected to a guide tray purified wastewater supply inside of a flowing rectangular open-topped tank, and at the outlet of the pipeline for drainage of a mixture of microalgae with residual wastewater is a microalgae separator to separate return and excess biomass. Conclusion. The proposed construction of photobioreactor can have good perspectives to be use in communal services for sewage water purification from biogenic compounds.